Looking for reliable answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Join our Q&A platform to get precise answers from experts in diverse fields and enhance your understanding. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
To solve the equation \(x^2 - 4x - 9 = 29\), follow these steps:
1. Rearrange the equation:
[tex]\[ x^2 - 4x - 9 = 29 \][/tex]
Move 29 to the left side to set the equation to equal zero:
[tex]\[ x^2 - 4x - 9 - 29 = 0 \][/tex]
Simplify the equation:
[tex]\[ x^2 - 4x - 38 = 0 \][/tex]
2. Recognize the form:
This is a standard quadratic equation of the form \(ax^2 + bx + c = 0\), where:
\(a = 1\),
\(b = -4\),
\(c = -38\).
3. Use the quadratic formula to solve for \(x\):
The quadratic formula is:
[tex]\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
4. Substitute the values of \(a\), \(b\), and \(c\):
[tex]\[ x = \frac{-(-4) \pm \sqrt{(-4)^2 - 4(1)(-38)}}{2(1)} \][/tex]
Simplify the terms:
[tex]\[ x = \frac{4 \pm \sqrt{16 + 152}}{2} \][/tex]
Combine the terms inside the square root:
[tex]\[ x = \frac{4 \pm \sqrt{168}}{2} \][/tex]
5. Simplify the square root and the fraction:
Notice that:
[tex]\[ \sqrt{168} = \sqrt{4 \cdot 42} = 2\sqrt{42} \][/tex]
So substitute back:
[tex]\[ x = \frac{4 \pm 2\sqrt{42}}{2} \][/tex]
Factor out the 2 in the numerator:
[tex]\[ x = \frac{2(2 \pm \sqrt{42})}{2} \][/tex]
Cancel out the 2:
[tex]\[ x = 2 \pm \sqrt{42} \][/tex]
6. Interpret the final solutions:
[tex]\[ x = 2 + \sqrt{42} \][/tex]
and
[tex]\[ x = 2 - \sqrt{42} \][/tex]
So the solution for the equation \(x^2 - 4x - 9 = 29\) is:
[tex]\[ x = 2 \pm \sqrt{42} \][/tex]
1. Rearrange the equation:
[tex]\[ x^2 - 4x - 9 = 29 \][/tex]
Move 29 to the left side to set the equation to equal zero:
[tex]\[ x^2 - 4x - 9 - 29 = 0 \][/tex]
Simplify the equation:
[tex]\[ x^2 - 4x - 38 = 0 \][/tex]
2. Recognize the form:
This is a standard quadratic equation of the form \(ax^2 + bx + c = 0\), where:
\(a = 1\),
\(b = -4\),
\(c = -38\).
3. Use the quadratic formula to solve for \(x\):
The quadratic formula is:
[tex]\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
4. Substitute the values of \(a\), \(b\), and \(c\):
[tex]\[ x = \frac{-(-4) \pm \sqrt{(-4)^2 - 4(1)(-38)}}{2(1)} \][/tex]
Simplify the terms:
[tex]\[ x = \frac{4 \pm \sqrt{16 + 152}}{2} \][/tex]
Combine the terms inside the square root:
[tex]\[ x = \frac{4 \pm \sqrt{168}}{2} \][/tex]
5. Simplify the square root and the fraction:
Notice that:
[tex]\[ \sqrt{168} = \sqrt{4 \cdot 42} = 2\sqrt{42} \][/tex]
So substitute back:
[tex]\[ x = \frac{4 \pm 2\sqrt{42}}{2} \][/tex]
Factor out the 2 in the numerator:
[tex]\[ x = \frac{2(2 \pm \sqrt{42})}{2} \][/tex]
Cancel out the 2:
[tex]\[ x = 2 \pm \sqrt{42} \][/tex]
6. Interpret the final solutions:
[tex]\[ x = 2 + \sqrt{42} \][/tex]
and
[tex]\[ x = 2 - \sqrt{42} \][/tex]
So the solution for the equation \(x^2 - 4x - 9 = 29\) is:
[tex]\[ x = 2 \pm \sqrt{42} \][/tex]
We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.